Empowering Woman in Islamic Microfinance: Lesson from Grameen Bank in Bangladesh, BMT and MBK Venture Capital in Indonesia - Atiqi Chollisni Nasution (STES Islamic Village, 2013)
Recently, microfinance have become an important component toreduce poverty. By involving the poor in the economic activities,most of microfinance institutions (MFIs) have succeeded inrunning their programs and have been flourished to improve thequality of poor people life. This study indicated that womenentrepreneurs have contributed positively either to householdincome or economic development. However, their contributionshave not optimalized yet in the microfinance program. The studyattempts to describe and review the microfinance program thatmight encourage the development of empowering women. Theobjective is to analyze the successful of microfinance programsthat have been applicated by some famous MFIs namely GrameenBank in Bangladesh, MBK Venture Capital and BMT (Baitul Maalwa Tamwil) in Indonesia. It is found that BMT’s marketingstrategy and MBK’s financing services are the suitable criteriasto enhance the number of women entrepreneurs and optimalize theprofitability of MFI. Meanwhile, Grameen Bank’s managementmodel is useful for minimizing the risk of microfinance program.